The Perception Among Students of Sunan Gunung Jati Karawang Vocational School on Learning of VolleyBall - Khuromadhan, Mochammad Gilang; Ismaya, Bambang; Dimyati, Akhmad; izzuddin, Deden akbar (Universitas Suryakancana, 2021)
This study aims to determine the perceptions of class XII students towards volleyball learning. To find out students' perceptions, the researchers conducted indicators, such as internal factors including attention, mood, experience and memory, while external factors included the uniqueness and contrast of the stimulus, the size and placement of objects or stimuli, motion or movement. The research method uses a survey method using a questionnaire. This research is quantitative descriptive. The population used was the entire class XII. The sampling technique used was the Cluster Random Sampling Technique, Specification Probability Sampling. The sample in this study is one class of five classes. The instrument used in this study used a questionnaire. The score used is the Likert scale. The results of this study indicate that the perceptions of class XII students towards volleyball learning at SMK Sunan Gunung Jati Karawang are in the